Study the Effect on Activity of Alumina Supported CuO-CeO2-ZrO2 Catalysts Prepared by Four Methods for CO Oxidation - Gaurav Rattan; R. Prasad (ASEAN Journal of Chemical Engineering, 2014)
In the present study four catalysts, prepared by four different methods i.e. co- impregnation, citric acid sol-gel, urea nitrate combustion and urea gelation co- precipitation methods, have been used to study the effect of CO oxidation. The precursor Cu(NO3) 23H2O has been used as for the preparation of catalysts having the composition CuCe5.17Zr3.83Ox/-Al2O3(25wt%). Catalysts were calcined at 5000C and characterized by BET, XRD, TGA/DSC and SEM. A fixed weight (100 mg) of the catalyst was taken in a tubular fixed bed reactor at atmospheric pressure. 2.0% CO in air at a total feed rate of 60 ml/min was used in the reactor. The oxidation of CO to carbon dioxide was carried out at temperature ambient to 280oC. The preparation methods effect the catalytic activity of the catalysts as is discussed in the results. Excellent activity for CO oxidation is shown by the catalyst prepared by sol – gel method followed by co-impregnation, urea gelation and urea nitrate combustion methods. It exhibited the total conversion at 210oC. All the four catalysts prepared did not show any deactivation activity for 50 hours of continuous runs.